Preliminary experience in laparoscopic distal pancreatectomy using the AEON™ endovascular stapler - Sheen, Aali J.; Bandyopadhyay, Samik; Baltatzis, Minas; Deshpande, Rahul; Jamdar, Saurabh; Carino, Nicola de Liguori (Frontiers in Oncology, 2023)
Background The aim of this study is to investigate the effects of using a new innovative endovascular stapler, AEON™, on the pancreatic leak rates and other outcome measures. Methods In a retrospective review of prospectively collected data from a secure tertiary unit registry, patients undergoing distal or lateral pancreatectomy were analyzed for any differences on pancreatic fistula rates, length of stay, comprehensive complication index (CCI), and demographics after using AEON™ compared with other commonly used staplers. Statistical significance was defined as <0.05. Results There were no differences in the demographics between the two groups totaling 58 patients over 2 years from 2019 to 2021. A total of 43 and 15 patients underwent pancreatic transection using other staplers and AEON™ endovascular stapler, respectively. The comparison of the two groups revealed a significantly reduced rate of mean drain lipase at postoperative day 3 with AEON™ (446 U/L) versus the other staplers (4,208 U/L) (p = 0.018) and a subsequent reduction of postoperative pancreatic fistula (POPF) from 65% to 20%. A reduction in the mean CCI, from 13.80 when other staplers were used to 4.97 when AEON™ was used, was also observed (p = 0.087). Mean length of stay was shorter by 3 days in the AEON™ group compared with that in the other staplers (6 and 9 days, respectively; p = 0.018). Conclusion AEON™ stapler when used to transect the pancreas demonstrated a significantly reduced pancreatic fistula rate, length of stay in hospital, and a leaning towards a reduced CCI. Its use should be further evaluated in larger cohorts with the encouraging results to determine whether this is possibly related to the technology used in the design of the AEON™ stapler.